Impacts of the COVID-19 Pandemic on Pediatric Type 1 Diabetes Management: A Qualitative Study. Issue 6 (December 2022) - Ferguson, Kacey; Moore, Hailey; Kaidbey, Jasmine H.; Khattak, Shazmenna; Saeed, Abbas; Cogen, Fran R.; Streisand, Randi; Sylvetsky, Allison C.
Purpose: The purpose of this study was to understand impacts of the coronavirus (COVID-19) pandemic on pediatric type 1 diabetes management. Methods: In-depth qualitative interviews were conducted with 15 parents of children (age 6-12 years) with type 1 diabetes. Parents responded to 8 open-ended questions about their experiences managing their children's type 1 diabetes during the COVID-19 pandemic. All interviews were transcribed, coded, and analyzed using qualitative thematic methods. Results: Parents reported both positive and negative aspects of managing their children's type 1 diabetes during the COVID-19 pandemic. Facilitators of diabetes management included spending more time together at home and enhanced convenience of telehealth appointments and online supply ordering. Parents also described difficulties managing their children's type 1 diabetes during the COVID-19 pandemic, including a lack of structure in their child's daily routine, which led to increases in sedentary behavior. Furthermore, they reported psychosocial challenges of type 1 diabetes management, which were exacerbated by the pandemic. Conclusion: While the COVID-19 pandemic was described as having overall positive impacts on pediatric type 1 diabetes management, efforts to support parents in increasing children's physical activity and reducing screen time are needed, along with readily accessible mental health resources for both parents and their children with type 1 diabetes.